2014
DOI: 10.15193/zntj/2014/92/173-186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enzymatic Preparations and Baking Methods on Selected Parameters of Wheat-Oat Bread

Abstract: MAGDALENA FUJARCZUK, ANNA CZUBASZEK, AGATA WOJCIECHOWICZ-BUDZISZ, MIROSŁAW ŻMIJEWSKI  WPŁYW PREPARATÓW ENZYMATYCZNYCH I METODY WYPIEKU NA WYBRANE CECHY CHLEBA PSZENNO-OWSIANEGO S t r e s z c z e n i e Celem przeprowadzonych badań była ocena zmian cech jakościowych pieczywa, otrzymanego z mieszanek mąki pszennej z różnym udziałem śruty owsianej, pod wpływem dodatku preparatów enzymatycznych i metody wypieku. Do badań użyto mąki pszennej typu 650 oraz mieszanek mąki pszennej i śruty owsianej. Udział śruty owsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
4
0
0
Order By: Relevance
“…On the other hand, the 25 and 30% samples, significantly deteriorated the value of the examined features (Table 3). These results were consistent with the research of other authors (Flander et al , 2007; Fujarczuk et al , 2014), who have shown that the addition of 15% of oat flour to a blend with wheat flour improves the bread's physical properties. However, higher additions, namely, 25 and 30% impacts negatively on its baking values.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the 25 and 30% samples, significantly deteriorated the value of the examined features (Table 3). These results were consistent with the research of other authors (Flander et al , 2007; Fujarczuk et al , 2014), who have shown that the addition of 15% of oat flour to a blend with wheat flour improves the bread's physical properties. However, higher additions, namely, 25 and 30% impacts negatively on its baking values.…”
Section: Resultssupporting
confidence: 93%
“…The lowest value for the L * parameter was shown by the bread crumb with 30% of oat flour addition. These results are consistent with those obtained in studies by Salehifar and Shahedi (2007) as well as Fujarczuk et al (2014). The values of C * parameter of bread crumb with oat flour additions were significantly different from those obtained in the control wheat bread test.…”
Section: Resultssupporting
confidence: 92%
“…The highest chewiness, similar to gumminess, was observed in the frozen bread rolls, whereas the lowest was observed in the standard and the prebaked bread rolls. The obtained results fit those obtained by Fujarczuk, Czubaszek, Wojciechowicz‐Budzisz, and Żmijewski (), who noted an increase in chewiness in the case of bread obtained from unfrozen raw chunks of dough. The standard bread rolls were characterized by the highest crumb resilience, and the lowest was noted in case of the frozen and the prebaked ones.…”
Section: Resultssupporting
confidence: 88%
“…The obtained results fit those obtained by Fujarczuk, Czubaszek, Wojciechowicz-Budzisz, and _ Zmijewski (2014), who noted an increase in chewiness in the case of bread obtained from unfrozen raw chunks of dough. The standard bread rolls were characterized by the highest crumb resilience, and the lowest was noted in case of the frozen and the prebaked ones.…”
Section: Texture Analysissupporting
confidence: 89%